Positional income concerns: Prevalence and relationship with personality and economic preferences - Tim Friehe; Mario Mechtel; Markus Pannenberg (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2014)
This paper presents detailed evidence about who compares to whom in terms of relative income. We rely on representative survey data on the importance of income comparisons vis-á-vis seven reference groups, allowing us to exploit within-subject heterogeneity. We explore the prevalence and determinants of positional income concerns, investigating the role of personality and economic preferences. Our results establish robust relationships between positional income concerns and the personality traits agreeableness, conscientiousness, and neuroticism, some of which depend on the reference group. Furthermore, risk and fairness preferences are significantly correlated with positional income concerns.
Keywords: D03; D12; D63; 330; relative income; status; personality; Big Five; survey; SOEP; economic preferences; risk; fairness